2017
DOI: 10.1097/prs.0000000000003832
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioid Use among Opioid-Naive Women Undergoing Immediate Breast Reconstruction

Abstract: Risk, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
84
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 58 publications
9
84
0
Order By: Relevance
“…Given the excellent long‐term survival from breast cancer, such patients are at risk of chronic opioid abuse that is not necessarily related to cancer pain . Recent studies have suggested that exposing opioid naïve patients to postoperative opioids converts approximately 10% of cancer patients undergoing curative‐intent oncology operations into chronic opioid users . Thus, it is paramount that surgeons minimize patient exposure to opioids while optimizing evidence‐based postoperative analgesia…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the excellent long‐term survival from breast cancer, such patients are at risk of chronic opioid abuse that is not necessarily related to cancer pain . Recent studies have suggested that exposing opioid naïve patients to postoperative opioids converts approximately 10% of cancer patients undergoing curative‐intent oncology operations into chronic opioid users . Thus, it is paramount that surgeons minimize patient exposure to opioids while optimizing evidence‐based postoperative analgesia…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Recent studies have suggested that exposing opioid naïve patients to postoperative opioids converts approximately 10% of cancer patients undergoing curative-intent oncology operations into chronic opioid users. 23,24 Thus, it is paramount that surgeons minimize patient exposure to opioids while optimizing evidencebased postoperative analgesia. 25 Although this is the largest study demonstrating opioid prescription preferences of breast surgical oncologists, there are several potential study limitations.…”
mentioning
confidence: 99%
“…The need for an opioid prescription may extend beyond a few months after surgery in 10% of patients undergoing breast reconstructive surgery,4 and long-term use may ultimately lead to complications. The development of a chronic pain syndrome as a complication is not uncommon and can occur in 20%–60% of patients 5…”
Section: Introductionmentioning
confidence: 99%
“…The stark increase in opioid misuse has led to a growing body of research focusing on the prescribing of opioids for postoperative pain, with many finding that most of the opioids prescribed postoperatively go unused . Therefore, understanding opioid needs and prescribing patterns after specific operations is essential .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have determined that the majority of patients undergoing general surgery procedures would have their pain needs met with less than 15 opioid pills (equivalent to 5 mg of oxycodone), and between 10 and 15 pills for oncologic breast‐specific surgery . Furthermore, it has been shown that new persistent opioid use is common following breast surgery, with 10% of patients undergoing breast surgery with immediate breast reconstruction (IBR) requiring opioids beyond 3 months postoperatively . The opioid requirements across the breadth of breast cancer operations and patient factors are less well understood than for other general surgery procedures .…”
Section: Introductionmentioning
confidence: 99%